2019
DOI: 10.1007/s10071-019-01301-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of associative learning process on the response of fledgling great tits (Parus major) to mobbing calls

Abstract: When they detect a predator, many species emit antipredator vocalizations. In some cases, they emit mobbing calls, which are associated with the caller approaching and harassing the predator while attracting others to join it. Surprisingly, although mobbing has been widely reported in adults of numerous species, there has been no test of the role of learning in mobbing call recognition, especially during ontogeny. Here, we exposed wild great tit (Parus major) nestlings to playbacks of an unthreatening, novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Tests were carried out between 06:00 and 13:00 hr during calm and dry days. To avoid pseudoreplication, all selected focal birds were distant from one another by at least 100 m (Dutour, Léna, et al., 2019; Dutour et al, 2020). Two or three different calling males were usually detected within 100 m, we never went on the same path twice, and we made sure that no bird was following us.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tests were carried out between 06:00 and 13:00 hr during calm and dry days. To avoid pseudoreplication, all selected focal birds were distant from one another by at least 100 m (Dutour, Léna, et al., 2019; Dutour et al, 2020). Two or three different calling males were usually detected within 100 m, we never went on the same path twice, and we made sure that no bird was following us.…”
Section: Methodsmentioning
confidence: 99%
“…Studies about the mechanisms underlying heterospecific communication suggest that both learning and innate processes are in place: associative learning has been evidenced both in the adult response to mobbing calls and in the ontogeny of mobbing behaviour in fledglings (Carlson et al., 2019; Dutour, Léna, et al., 2019; Magrath et al., 2015; Potvin et al., 2018). This could well explain higher responsiveness towards sympatric species than towards allopatric ones (Wheatcroft & Price, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…if calls are acoustically similar among species [26][27][28]), or learned [24,29], which may occur as early as the embryonic stage in birds [30]. In addition to learning heterospecific alarm calls, recent experimental evidence has shown that birds and mammals can learn to associate unfamiliar acoustic cues with perceived predation risk [14,31,32], adding to a growing body of literature suggesting that associative learning may be the mechanism underpinning the recognition of heterospecific alarm calls. Recent research has also shown that birds can learn to associate novel sounds with heterospecific alarm calls [15], suggesting that a behavioural response to an acoustic cue can be socially transmitted, even when the cue is not initially recognized as an alarm call.…”
Section: Introductionmentioning
confidence: 99%
“…The response to alarm calls may be to run to shelter, increase vigilance or mob the potential predator (Dutour et al., 2019; Sherman, 1985), and the ability to respond appropriately to a call can be either innate (e.g., white‐browed scrubwren, Sericornis frontali, Platzen & Magrath, 2004) or learned (e.g., Belding's ground squirrels, Urocitellus beldingi , Mateo & Holmes, 1997). In addition to information gained from conspecific alarm calls, information on potential predators may also be gained by eavesdropping on the signals or cues made by heterospecific individuals (Magrath et al., 2015; Meise et al., 2018).…”
Section: Introductionmentioning
confidence: 99%